2002
DOI: 10.1177/10432302012006003
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Women: Making Connections to Community Resources for Support in Family Caregiving

Abstract: The purpose of this ethnographic study was to understand how immigrant women caregivers accessed support from community resources and identify the barriers to this support. The study included 29 Chinese and South Asian women caring for an ill or disabled child or adult relative. All experienced barriers to accessing community services. Some possessed personal resources and strategies to overcome them; others remained isolated and unconnected. Family and friends facilitated connections, and a connection with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 0 publications
3
68
0
Order By: Relevance
“…Both the review and the consultation showed that language can inhibit access to health care for carers whose first or preferred language is not English (Katbamna et al, 1998a;Gerrish, 2001;Neufield et al, 2002). One solution is to make more use of interpreting services, yet Gerrish (2001) found that district nurses rarely use these services.…”
Section: Barriers Related To Language or Culturally Held Beliefs And mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the review and the consultation showed that language can inhibit access to health care for carers whose first or preferred language is not English (Katbamna et al, 1998a;Gerrish, 2001;Neufield et al, 2002). One solution is to make more use of interpreting services, yet Gerrish (2001) found that district nurses rarely use these services.…”
Section: Barriers Related To Language or Culturally Held Beliefs And mentioning
confidence: 99%
“…Recent immigrant and refugee carers face wide-ranging access problems (such as language difficulties, racism, discrimination, lack of knowledge, uncertain status, limited means and social support) given their unfamiliarity with the types of services available (Neufield et al, 2002).…”
Section: Barriers Related To Language or Culturally Held Beliefs And mentioning
confidence: 99%
“…The work of Edwards (1998), Neufeld et al (2002), Riessman (2000) and Temple (2002) are all examples of a move away from an attempt solely to find equivalence between words across languages and reflexively debate with the translators the choices they had to make in producing written text. For example, Temple's work with Asian Support Workers (2002) involved the two workers collecting the data and carrying out research on mental health issues with Asian communities.…”
Section: T R a N S L Ato R S Wo R K I N G W I T H R E S E A Rc H E R Smentioning
confidence: 99%
“…Neufeld et al's (2002) ethnographic study of how immigrant Chinese and South Asian women caregivers in Canada accessed support from community resources used a similar method of employing translators to collect data, transcribe it and participate in discussions about its interpretation. Edwards (1998), Neufeld et al (2002) and Temple (2002) specifically concern themselves with word and concept choice and the transcription/ translation process. Edwards made a decision in her research to encourage the interpreter/translator to use the third person rather than translate literally what someone had said.…”
Section: T R a N S L Ato R S Wo R K I N G W I T H R E S E A Rc H E R Smentioning
confidence: 99%
“…Often, the migration motivation of a male figure is the primary focus of immigration scholarship, with a female partner seen as a secondary actor who follows a husband or boyfriend to the new host country (Cerrutti & Massey, 2001;Glick, 2010); this is particularly true in literature on border crossing, which has focused primarily on Latino men (DeLuca, McEwen, & Keim, 2010;Infante, Idrovo, Sanchez-Dominguez, Vinhas, & GonzalezVazquez, 2012). However, women have their own considerations and experiences when migrating, particularly when responsible for the care of others (Neufield, Harrison, Stewart, Hughes, & Spitzer, 2002). The changing global economy has created economic opportunities for women, leading to the "feminization of migration" (Falicov, 2007, p. 160).…”
Section: Immigrant Women and The Migration Processmentioning
confidence: 99%